2019
DOI: 10.31235/osf.io/ujqma
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blended CEFR in Enhancing Vocabulary among Low Proficiency Students

Abstract: Emphasis on English language proficiency and digital literacy among Malaysian students in schools have been given utmost priority in the Malaysian Education Transformation (2013 -2025). With the introduction of Common European Framework of Reference (CEFR), (Council of Europe, 2001) the emphasize for low proficient students to acquire vocabulary knowledge is crucial for them to move progressively into the next band as stated in the CEFR global scales. Yet, concerns arises as how the implementation of (CEFR) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The achievements recorded in previous blended learning studies demonstrated a clear indicator of the positive effects of blended learning on students' achievement and performance across the four major skills of the English language (Huang, 2019;Challob, Nadzrah & Hafizah, 2016;Ghazidadeh & Fatemipour, 2017;Krishnan & Yunus, 2019;Shih et al, 2015;Said et al, 2013). Students with blended learning experiences showed improvement and developed proficiency at a higher rate as compared to their peers who did not.…”
Section: Influences and Successes Of Blended Learningmentioning
confidence: 88%
See 3 more Smart Citations
“…The achievements recorded in previous blended learning studies demonstrated a clear indicator of the positive effects of blended learning on students' achievement and performance across the four major skills of the English language (Huang, 2019;Challob, Nadzrah & Hafizah, 2016;Ghazidadeh & Fatemipour, 2017;Krishnan & Yunus, 2019;Shih et al, 2015;Said et al, 2013). Students with blended learning experiences showed improvement and developed proficiency at a higher rate as compared to their peers who did not.…”
Section: Influences and Successes Of Blended Learningmentioning
confidence: 88%
“…Students with blended learning experiences showed improvement and developed proficiency at a higher rate as compared to their peers who did not. Furthermore, a boost in students' motivation, participation and engagement during English lessons could be observed (Oweis, 2018;Albiladi & Alshareef, 2019;Krishnan &Yunus, 2019;Mustapha et al, 2010). The positive attitudes could be attributed to the integration of technology in teaching and learning, as it steered away from the common classroom environment with added fun and interactive elements.…”
Section: Influences and Successes Of Blended Learningmentioning
confidence: 96%
See 2 more Smart Citations